Applicability of Solid Anaerobic Digestion Sludge of the Lignocellulosic Residues to Soil Conditioning (ABSTRACT PAGE) - B. C. Qi; G. M. Wolfaardt (International Mineral Processing Congress, 2003)
"From a lifecycle point of view, biologically digested sludge is a valuable product that should be reused if possible. In contrast to landfill and incineration, application of digested sludge comprises the recycling nutrients and organic matter and reflects the policy of resource conservation and sustainability in waste management. Sludge may be applied to agricultural land for further sludge treatment and improvement of the characteristics of the soil. The characteristics of sludge that affect its applicability for soil conditioning include moisture content, pathogens, nutrients and metals. In this paper, the use of solid anaerobic digestion sludge of the lignocellulosic residues to condition soil was investigated in regards to nutrient composition, water content/retention capacity, hygienic quality (contamination of pathogenic bacteria) and heavy metal adsorbing/releasing characteristics of the sludge.The digested sludge had approximately 44.5% free and immobilized water and 46.9% bound water. The water-holding capacity of the sludge was high. This was the first merit to apply the sludge to agriculture in dry areas. Secondly, the sludge was rich in macro-nutrients (N, P, K) and a series of micro-nutrients (Ca, Mg, Mn, Na, Fe, Cu, Zn, B). The water-soluble fractions of macro-nutrients in the sludge were found considerably low. This implied that the loss or leaching of the macro-nutrients from the anaerobic sludge to the aqueous environment be slow. The nutrients loss owing to leaching could be reduced. However, because of a lower macro-nutrient content of the anaerobic sludge, comparable to the chemical fertilizer, it is advisable that the anaerobic sludge be applied together with commercial fertilizer to the agriculture land. Thirdly, the anaerobic sludge had strong selective adsorption affinity for heavy metal ions; non-heavy metal ions such as K(I) and Ca(II) could be released easily from the sludge in a wide pH range, such as pH from 1.0 to 8.0. Since the metal toxicity to the environment mainly comes from the mobile heavy metal ions, the selectivity to adsorb heavy metal ions of the anaerobic sludge can be utilized to reduce the availability of heavy metal ions to plants and humans in aquatic environment. Fourthly, the anaerobic digestion under thermophilic conditions showed a promising disinfecting effect to the sludge, in contrast to the landfill digestion."